The Formula of Romance in The Redeeming Love (2022) Movie - Jusrianti Jusrianti; Rasiah Rasiah; Arman Arman (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
This research aims to analyze the formula of romance in the Redeeming Love (2022) movie. The focus of the problem is the convention and invention formula of romance in the Redeeming Love (2022) movie. The theory of Formula from John G. Cawelti analyzes the problem. This research method is descriptive qualitative. From the analysis results, the researcher found convention and invention in the movie. In terms of convention, this movie still maintains the romance formula, such as (1) The romance plot still consists of their first meeting, the man winning the woman, the conflict, and the happy ending. (2) The figure of romance still the presence of the hero and heroine namely Michael and Angel. (3) The setting of romance consists of a place or setting on a hill, a time setting such as in the morning, afternoon, and evening, and an atmosphere setting such as happy, regretful, angry, tense, sad, worried, and afraid. As for the invention of new romance elements found in the movie, such as (1) Romance narrative structure using a mixed pattern of Cinderella pattern, Pamela pattern, and contemporary pattern, (2) The character of romance, such as the hero is described as an ordinary, popular and beautiful heroine, and heroine who has a stubborn nature, (3) The plot of romance, such as Hero gives up on heroine.